The Effect of Using the ZEP Quiz Application on Fifth-Grade Students’ Learning Outcomes in Pancasila Education - Nisdayanti Nisdayanti; Ahmad Ahmad; Ashari Usman (Journal of Education and Learning Sciences, 2025)
The development of digital technology has transformed the learning process in elementary schools, particularly through the integration of interactive digital learning media. One platform that can support this transformation is ZEP Quiz, a gamification-based learning application designed to create an engaging, interactive, and enjoyable learning environment. However, the learning process of Pancasila Education at SD Negeri 2 Konda is still predominantly conducted using conventional methods, which may limit student engagement and result in suboptimal learning outcomes. This study aimed to determine the effect of using the ZEP Quiz application on the learning outcomes of fifth-grade students in Pancasila Education. This study employed a quantitative approach using a quasi-experimental method with a Pretest–Posttest Control Group Design. The sample consisted of 58 fifth-grade students, comprising 31 students in the experimental class and 27 students in the control class, selected using a saturated sampling technique. Data were collected through learning outcome tests, observations, and documentation. The data were analyzed using descriptive statistics and inferential statistics, including the Shapiro–Wilk normality test, Levene’s test of homogeneity, and the Independent Samples t-Test. The results showed that students who learned using the ZEP Quiz application achieved higher learning outcomes than those who received conventional instruction. The hypothesis test revealed a significance value (Sig. 2-tailed) of less than 0.05, indicating a significant difference in learning outcomes between the experimental and control groups. Therefore, the use of the ZEP Quiz application had a positive and significant effect on the learning outcomes of fifth-grade students in Pancasila Education. These findings indicate that ZEP Quiz can serve as an innovative gamification-based digital learning medium to support more interactive and effective Pancasila Education learning in elementary schools.